1993
DOI: 10.1093/bja/70.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Articular Morphine for Pain Relief After Anterior Cruciate Ligament Repair

Abstract: We have performed a randomized, double-blind controlled study in patients undergoing elective anterior cruciate ligament repair, to assess the effect of intra-articular morphine on postoperative pain. The morphine group (n = 11) received morphine 5 mg in saline 25 ml and the control group (n = 9), saline 25 ml intra-articularly. Patients in the morphine group had significantly smaller pain scores throughout the 24-h postoperative period compared with those in the control group (P < 0.05). There was less requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
9

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 0 publications
3
57
0
9
Order By: Relevance
“…In four studies, IA morphine 5 mg in 25 ml of saline resulted in a significant reduction in postoperative pain for up to 24 h after various arthroscopic procedures [4,5] and after anterior cruciate ligament repair [6,7]. In none of these studies was a control for systemic effects of the locally administered morphine included .…”
Section: Discussionmentioning
confidence: 99%
“…In four studies, IA morphine 5 mg in 25 ml of saline resulted in a significant reduction in postoperative pain for up to 24 h after various arthroscopic procedures [4,5] and after anterior cruciate ligament repair [6,7]. In none of these studies was a control for systemic effects of the locally administered morphine included .…”
Section: Discussionmentioning
confidence: 99%
“…Bezieht man die ersteren 9 in die Bilanz mit ein, so kommen 7mal "pro" und 2mal "contra" hinzu und es steht 20,5 zu 10,5. [4,6,9,13,20,21,22,23,24,26,34,35,47] ("pro" in Tab. 1), 8 fanden keinen signifikanten Effekt gegen Plazebo [1,3,11,14,15,39,44,53] ("con" in Tabelle …”
Section: Zusammenfassungunclassified
“…Sie weisen ferner darauf hin, daß die bisherige Literatur von einer Eignung der PCA-Methode zur Evaluation der Wirksamkeit anderer Analgesieverfahren ausgehe. Auch JOSHI et al haben PCA-Pumpen zur Schmerzevaluation eingesetzt und damit einen Opioideffekt gefunden [23]. In ihrer Studie betrug der durchschnittliche Morphinverbrauch über 24 h in der Plazebogruppe 74 mg (!…”
Section: Kein Effekt Nach Leitungsblockaden?unclassified
See 1 more Smart Citation
“…These cytokines have a fundamental role in RA pathology, causing inflammation, pain and articular destruction (9). Previous studies have indicated that injection of opioids into knee joints after surgery caused prolonged post-operative analgesia in patients (10)(11)(12), which may be associated with their immunomodulatory function. Based on these results, the present study hypothesized that opioids also produce analgesic effects on RA via regulating peripheral inflammation.…”
Section: Introductionmentioning
confidence: 99%